Correction: Sirtuin-2 Regulates Sepsis Inflammation in ob/ob Mice - Wang, Xianfeng; Buechler, Nancy L.; Martin, Ayana; Wells, Jonathan; Yoza, Barbara; McCall, Charles E.; Vachharajani, Vidula (PLOS ONE, 2016)
null